System topologies and performance evaluation of the RESOLUTION embedded local positioning system - Mosshammer, Ralf; Eickhoff, Ralf; Huemer, Mario; Weigel, Robert (Elektrotechnik und Informationstechnik, 2008)
This article introduces a hybrid communications and positioning system, developed in the course of the EU-endorsed RESOLUTION project. The system provides a reconfigurable, embedded hardware platform fit to support a variety of deployment scenarios. The flexibility of our solution is assessed by means of a comprehensive system simulation.
elib2cris::1512001600,mosshammer2008